La « sous-filière » bureautique dans l’ensemble électronique : Perspectives internationales - Guir, Roger (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
In an age of electronic revolution, the conditions for global specialization have changed, be it from the nation's or from the fîrm's perspective. The logic behind the productive System is today even more integrative and systemic, hence upsetting the methods and concepts of economic and strategic analysis.In focussing on the sphere of office-automation in the channel of electronics, the analytical framework used has been that of a « sub-channel » in order to define the interdependence and the effects of the technological synergy which are characteristic of office-automation, and to deduce the major trends in the international division of labour. Thus the use of a new, more comprehensive channel appears to be better suited for the analysis of future trends in the international division of labour.